Assessment of Anti-Oxidant Potency of Small Chain Glycopeptides Using DPPH Free Radical Scavenging Assay - Kandasamy Nagarajan; Sneha Singh; Taleuzzaman; Sadaf J. Gilani; A. Mazumder (Journal of Pharmacy and Nutrition Sciences, 2012)
1,1-Diphenyl-2-picryl-hydrazyl (DPPH) in-vitro assay was employed to determine the antioxidant potency of test compounds I to VII [Arg-Thr-Starch (RTStr); Ser-Arg-Lac (SRLac); Asn-Arg-Mannose (NRMs); Arg-Asn-Lac (RNLac); Arg-Thr-Lac (RTLac); His-Asn-Mannose (HNMs); Asn-His-Lac (NHLac)] using ascorbic acid as the standard drug. The percentage scavenging activity of the test drugs were determined at different concentrations and the IC50 value of the test compounds were subsequently compared with that of ascorbic acid. Among the compounds tested, compound II (SRLac) showed highest antioxidant activity with an IC50value of 14.2 mg/ml whereas compounds I (RTS), VII (NHLac) and IV (RNLac) revealed the IC50 value of 14.3 mg/ml, 14.5 mg/ml and 15.7 mg/ml, respectively when compared with ascorbic acid (IC50 = 15.8 mg/ml). All the synthesized glycopeptides were further characterized by TLC, Melting point, IR, NMR and Mass spectral datas. Based on the above results, Ser-Arg-Lac could be considered as a lead compound for the development of new antioxidant drug for prevention of human diseases.